Innovation of the Process of Inventorying of the Selected Transport Units: Case Study in the Automotive Industry - Chocholáč, Jan; Boháčová, Ladislava; Kučera, Tomáš; Sommerauerová, Dana (My University, 2017)
In the current situation, highly competitive time when the emphasis is on shortening delivery schedules, streamlining the production cycle and, ultimately, reducing the total cost businesses are forced to optimizations and innovations. The article deals with the inventory of the selected transport units in warehouses. The inventory is currently being carried out through manual labor of employees. This paper proposes a possible implementation of new and innovative approach to inventory control, with the help of an automated inventory realized by the drones.
Inovace procesu inventarizace vybraných přepravních jednotek: případová studie v automobilovém průmyslu
Keywords: inventorying; transport units; automotive industry; logistic chain; inventarizace; přepravní jednotky; automobilový průmysl; logistický řetězec